Acute Severe Asthma in the Intensive Care Unit: From Bronchodilators to Extracorporeal Membrane Oxygenation - Parisa Abedi; Geoffrey Chupp; Gabriella Wilson; Sandra Zaeh; Astha Chichra (Journal of Intensive Care Medicine, 2026)
Acute severe asthma exacerbations are life-threatening critical care emergencies characterized by profound airflow obstruction, respiratory acidosis, and risk for cardiopulmonary arrest. For the purposes of this review, the term ‘acute severe asthma’ is used to encompass what has variably been described as near-fatal asthma, status asthmaticus, and life-threatening asthma in the literature. Early recognition of impending respiratory failure, timely intubation and a stepwise approach to supportive interventions are critically important to minimize the risk of mortality and optimize outcomes. Initial treatment focuses on prompt initiation of medical therapies to stabilize ventilation and prevent progression to respiratory failure. If intubated, ventilatory strategies aimed at reducing dynamic hyperinflation and auto-PEEP with permissive hypercapnia need to be considered. When conventional management fails or when barotrauma risk, acid base derangements or hypoxemia become life-threatening, venovenous extracorporeal membrane oxygenation (VV-ECMO) can be utilized as a bridge to recovery. Given its invasiveness, careful patient selection for VV-ECMO is essential. This review provides an overview of: 1) the pathophysiology of acute severe asthma exacerbations, 2) expert guidelines and 3) consensus on best practices for the optimal use of standard and adjunctive pharmacologic treatments and mechanical ventilation strategies, and 4) patient selection criteria for and the emerging role of VV-ECMO for the treatment of acute severe asthma.